2016
DOI: 10.1038/srep39435
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional ultrastructural analysis of cells in the periodontal ligament using focused ion beam/scanning electron microscope tomography

Abstract: The accurate comprehension of normal tissue provides essential data to analyse abnormalities such as disease and regenerative processes. In addition, understanding the proper structure of the target tissue and its microenvironment may facilitate successful novel treatment strategies. Many studies have examined the nature and structure of periodontal ligaments (PDLs); however, the three-dimensional (3D) structure of cells in normal PDLs remains poorly understood. In this study, we used focused ion beam/scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…In conventional single section analysis, PDL cells are generally oriented with their long axes parallel to the direction of the PDL fibers. We have previously reported that, in 3D images, PDL cells exhibit a flat shape with long processes that are wing‐like, rather than spindle‐shaped. We showed that these PDL cells were in contact with neighboring cells and formed a widespread mesh‐like network between the cementum and alveolar bone.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In conventional single section analysis, PDL cells are generally oriented with their long axes parallel to the direction of the PDL fibers. We have previously reported that, in 3D images, PDL cells exhibit a flat shape with long processes that are wing‐like, rather than spindle‐shaped. We showed that these PDL cells were in contact with neighboring cells and formed a widespread mesh‐like network between the cementum and alveolar bone.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, focused ion beam/scanning electron microscope tomography (FIB/SEM tomography) has been developed, 8,9 which facilitates observation of hundreds of serial sections, reconstruction of 3D structures with high resolution and quantitative analysis of structural properties. We have previously reported the 3D ultrastructural properties of PDL cells, 10 and of other tissues [11][12][13][14][15][16][17] and organelles 18,19 after performing a quantitative analysis using FIB/SEM tomography.…”
Section: Introductionmentioning
confidence: 99%
“…The specimens were prepared as previously described. 24 26 Briefly, after washing five times with the cacodylate buffer, the specimens were postfixed for 30 minutes in a solution containing 2% osmium tetroxide and 1.5% potassium ferrocyanide in the cacodylate buffer at 4°C. The specimens were then washed five times with distilled water and immersed in 1% thiocarbohydrazide solution for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Specimens were prepared for FIB/SEM tomography as described previously [35][36][37] , with some modifications. On days 7 and 14, the cell cultured membranes were fixed with 2% paraformaldehyde and incubated in 2.5% glutaraldehyde in 0.1 M cacodylate (pH 7.3) buff er for 15 min at room temperature for fi xation.…”
Section: Fib/sem Tomography Of Cultured Membranesmentioning
confidence: 99%